Evaluating the efficacy of mind maps and micro-videos in postoperative care education for lung cancer patients - Liang Feng; Wenjun Shen; Chen Zhang; Dandan Liu; Shunyi Huang; Xiaoxin Liu (Discover Oncology)
Abstract Background Early health education is crucial for lung cancer patients and their families to learn self-monitoring and how to seek appropriate help for existing or upcoming issues. Mind maps and micro-videos are effective tools in various chronic disease and perioperative care settings, but their application in lung cancer care is relatively understudied. This study aims to explore the efficacy of early, continuous health education using mind maps and micro-videos in the postoperative care of lung cancer patients. Objective The primary objective of this study is to evaluate the impact of mind maps and micro-videos on key health-related outcomes in postoperative care for lung cancer patients, including patient satisfaction, health education knowledge, nursing compliance, social support, and quality of life. Methods This study enrolled 133 postoperative lung cancer patients who were admitted to the special ward of Shanghai Chest Hospital, affiliated with Shanghai Jiaotong University School of Medicine, from January 2022 to December 2023. Patients were randomly assigned to either the control group (n = 65) or the intervention group (n = 68), ensuring comparable baseline characteristics. Baseline characteristics, including age, gender, and clinical stage, were comparable between the control and intervention groups (p > 0.05), supporting the validity of the observed differences in outcomes. The control group received routine care and verbal education, while the intervention group received additional systematic, comprehensive, and standardized health education through mind maps and micro-videos. Outcomes measured included patient satisfaction with health education, knowledge of health education, nursing compliance, social support, and quality of life. Results Post-intervention, the intervention group showed significantly higher scores in patient satisfaction (80.25 ± 2.11 vs. 72.18 ± 4.57, p < 0.05), health education knowledge (80.03 ± 4.26 vs. 69.85 ± 5.36, p < 0.05), nursing compliance (96.92% vs. 86.15%, p < 0.05), social support (52.33 ± 6.71 vs. 38.67 ± 5.88, p < 0.05), and quality of life (82.8 ± 4.5 vs. 75.8 ± 5.4, p < 0.05) compared to the control group. Conclusion The use of mind maps and micro-videos in health education significantly improves the postoperative care outcomes for lung cancer patients. These tools enhance patient satisfaction, knowledge, compliance, social support, and quality of life, demonstrating their efficacy in clinical settings.